Correlating carbon and oxygen isotope events in early to middle Miocene shallow marine carbonates in the Mediterranean region using orbitally tuned chemostratigraphy and lithostratigraphy. (13th April 2015) - Auer, Gerald; Piller, Werner E.; Reuter, Markus; Harzhauser, Mathias
Abstract During the Miocene prominent oxygen isotope events (Mi‐events) reflect major changes in glaciation, while carbonate isotope maxima (CM‐events) reflect changes in organic carbon burial, particularly during the Monterey carbon isotope excursion. However, despite their importance to the global climate history they have never been recorded in shallow marine carbonate successions. The Decontra section on the Maiella Platform (central Apennines, Italy), however, allows to resolve them for the first time in such a setting during the early to middle Miocene. The present study improves the stratigraphic resolution of parts of the Decontra section via orbital tuning of high‐resolution gamma ray (GR) and magnetic susceptibility data to the 405 kyr eccentricity metronome. The tuning allows, within the established biostratigraphic, sequence stratigraphic, and isotope stratigraphic frameworks, a precise correlation of the Decontra section with pelagic records of the Mediterranean region, as well as the global paleoclimatic record and the global sea level curve. Spectral series analyses of GR data further indicate that the 405 kyr orbital cycle is particularly well preserved during the Monterey Event. Since GR is a direct proxy for authigenic uranium precipitation during increased burial of organic carbon in the Decontra section, it follows the same long‐term orbital pacing as observed in the carbon isotope records. The 405 kyr GR beat is thus correlated with the carbon isotope maxima observed during the Monterey Event. Finally, the Mi‐events can now be recognized in the δ18O record and coincide with plankton‐rich, siliceous, or phosphatic horizons in the lithology of the section.